2003
DOI: 10.1182/blood-2002-06-1743
|View full text |Cite
|
Sign up to set email alerts
|

The resistance of B-CLL cells to DNA damage-induced apoptosis defined by DNA microarrays

Abstract: B-cell chronic lymphoid leukemia (B-CLL) is a highly heterogeneous human malignancy, presumably reflecting specific molecular alterations in gene expression and protein activity that are thought to underlie the variable disease outcome. Most B-CLL cell samples undergo apoptotic death in response to DNA damage. However, a clinically distinct aggressive subset of B-CLL is completely resistant in vitro to irradiation-induced apoptosis. We therefore addressed 2 series of microarray analyses on 4 sensitive and 3 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 48 publications
(55 reference statements)
2
64
0
2
Order By: Relevance
“…Radiation-induced ceramide has been shown to promote membrane-associated receptor activation by facilitating the clustering of receptors within lipid rafts [Balaban et al, 1996, Goldkorn et al, 1997. The inducible alteration in gene expression is a fundamental molecular event of mammalian cells in response to ionizing radiation, and the fate of cells will at least partially depend upon the inducible changes in expression of some genes involved in these complex regulatory pathways resulting in cell cycle delays, cell killing or apoptosis and DNA repair [Chaudhry et al, 2003, Cucinotta et al, 2002Vallat et al, 2003. The cDNA microarray technology, allowing a large-scale expression profiling analysis, can provide tremendous information for elucidating the complex cellular response to radiation.…”
Section: Radiation Response Genes In Breast Cancer Cellsmentioning
confidence: 99%
“…Radiation-induced ceramide has been shown to promote membrane-associated receptor activation by facilitating the clustering of receptors within lipid rafts [Balaban et al, 1996, Goldkorn et al, 1997. The inducible alteration in gene expression is a fundamental molecular event of mammalian cells in response to ionizing radiation, and the fate of cells will at least partially depend upon the inducible changes in expression of some genes involved in these complex regulatory pathways resulting in cell cycle delays, cell killing or apoptosis and DNA repair [Chaudhry et al, 2003, Cucinotta et al, 2002Vallat et al, 2003. The cDNA microarray technology, allowing a large-scale expression profiling analysis, can provide tremendous information for elucidating the complex cellular response to radiation.…”
Section: Radiation Response Genes In Breast Cancer Cellsmentioning
confidence: 99%
“…29 This also holds true for blk, a gene encoding an SRC (sarcoma virus) kinase found to be downregulated in B-cell chronic lymphocytic leukemia cells that were resistant to DNA damageinduced apoptosis. 30 Of importance, in Ph chromosomepositive leukemia a role of tyrosine kinases has been stated for reducing BCR-ABL dependence and for reducing imatinib efficacy. 13 In addition, it has been suggested that downregulation of tumor necrosis factor receptor-associated protein 1 (TRAP1), a member of the heat-shock family of proteins, might play an important role in the induction of apoptosis potentially caused by the formation of reactive oxygen species (ROS).…”
Section: Tablementioning
confidence: 99%
“…Furthermore, c-IAP1 was identified by gene expression profiling as one of the genes that was upregulated in CLL cells, which were resistant to DNA damage-induced apoptosis, compared with sensitive samples. 58 By comparison, immunocytochemical analysis of c-IAP1, c-IAP2 and XIAP expression in CLL patients revealed no correlation between expression levels of IAP proteins and sensitivity to fludarabine-induced apoptosis or prognostic factors, 59 indicating that IAP protein expression was not generally linked to defective DNA-damage response. Moreover, gene expression profiling of the IAP genes in hematological malignancies unraveled a specific pattern of expression of c-IAP1, c-IAP2 and survivin in CLL, B-cell ALL and follicular lymphoma samples that discriminated these diseases from each other and from other entities.…”
mentioning
confidence: 99%